Flotation of hydrophobic minerals in Hallimond tube - Błaszków, Aleksandra; Ratajczak, Tomasz; Szyszka, Danuta (Wydział Geoinżynierii, Górnictwa i Geologii Politechniki Wrocławskiej, 2024)
This study analyses the effect of hydrophobicity on the floatability of sulphur, silicon, fluorite and galena. Flotation was performed in a Hallimond tube in distilled water and in the presence of a frother (α-terpineol). The results confirm that all the analysed minerals showed floatability in distilled water, with a varying yield, depending on the contact angle and density of each mineral. The introduction of a frother significantly improved the flotation efficiency, mainly for sulphur, silicon and fluorite.
Mining Science, Vol. 31, 2024, s. 219-227
Keywords: górnictwo; geologia; geoinżynieria; froth flotation; hydrophobic minerals; contact angle; Hallimond tube; flotometry